Study on Self-Excited Oscillation Suppression of Supersonic Inlet Based on Parallel Cavity - Cai, FeiChao; Huang, Xing (Frontiers in Energy Research, 2022)
Aiming at the problem of self-excited oscillation in a supersonic inlet, the oscillation suppression of parallel cavities in a shock system is studied. Based on the shock dynamic model, the theoretical calculation model of parallel cavity under dynamic shock is established, and the effects of cavity volume and oscillation frequency on shock oscillation flow field parameters are analyzed. On this basis, an integrated numerical model including cavity and inlet and outflow fields is established, and the effects of cavity on the inlet flow field parameter distribution and parameter oscillation are compared by using unsteady numerical calculation algorithm. The theoretical calculation results show that the parallel cavity can reduce the amplitude of flow field pressure oscillation, and increasing the cavity volume is beneficial to suppress parameter oscillation. The unsteady numerical calculation of three groups of working conditions shows that the cavity changes the amplitude of parameter oscillation, and the high amplitude frequency point also decreases compared to the model without cavity. Through the alternating change of pressure between the channel and cavity during the movement of the shock wave, the cavity gas filling and overflow dampen the shock wave forward and pressure change of the mainstream, so as to suppress the self-excited oscillation.